Flexible Liquid-Cooled Electromagnetic Gripper for Grasping Heavy Objects - Mauricio Rodriguez Calvo; Toshihiro Nishimura; Tetsuyou Watanabe (IEEE Access, 2025)
This paper presents a novel electromagnetic gripper designed for grasping heavy objects (up to 20 kg) with self-adaptability grasping. The gripper features Liquid-Cooled Electromagnetic Actuators with Dual-Pole Actuation (LEA-DAs) serving as fingertips and a Wire Length Retention Mechanism (WLRM). Both poles are used simultaneously to provide a high payload and grip stability. The LEA-DAs are cooled by a closed-loop oil system, which allows the gripper to maintain high power output while ensuring safe operating temperatures for an electromagnetic drive. A method has been adopted to enable the grasping of objects of various sizes and shapes, where the object is enclosed and grasped using a wire. The wire’s length is fine-tuned to match the object’s shape and size through a Rear Pole Actuation Mechanism (RPAM), while a WLRM keeps the wire in its fully extended state, enabling it to conform to the shape of the object and facilitating its release. The RPAM enhances grip stability across diverse geometries. Testing with objects of various cross-sections, including circular, hexagonal, and rectangular shapes, demonstrates that the combination of high grasping force and an adaptable grip structure allows the gripper to grasp heavy objects effectively. This study presents an analysis of the mechanisms to achieve the desired results. The gripper is studied experimentally through grasping tests.